2013
DOI: 10.1002/oby.20647
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing identifies variation in CYB5A and RNF10 associated with adiposity and type 2 diabetes

Abstract: Objective Few coding variants in genes associated with type 2 diabetes (T2D) have been identified, and the underlying physiologic mechanisms whereby susceptibility genes influence T2D risk are often unknown. The objective of this study was to identify coding variation that increases risk for T2D via an effect on a pre-diabetic trait. Design and Methods Whole exome sequencing was done in 177 Pima Indians. Selected variants (N=345) were genotyped in 555 subjects characterized for body fatness, glucose disposal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Compared to large outbred populations, isolated populations show extended patterns of linkage disequilibrium (LD), and a higher probability for the presence of disease-associated variants with high frequency due to genetic drift and selection [3,4]. These properties are advantageous for genetic-association studies, which have recently been demonstrated in various isolated populations by the discovery of novel variants associated with cardio-metabolic traits [5][6][7][8][9][10][11][12][13], and of particular interest coding variants in CREBRF and ADCY3 have been associated with obesity in Samoans and Greenlanders, respectively [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to large outbred populations, isolated populations show extended patterns of linkage disequilibrium (LD), and a higher probability for the presence of disease-associated variants with high frequency due to genetic drift and selection [3,4]. These properties are advantageous for genetic-association studies, which have recently been demonstrated in various isolated populations by the discovery of novel variants associated with cardio-metabolic traits [5][6][7][8][9][10][11][12][13], and of particular interest coding variants in CREBRF and ADCY3 have been associated with obesity in Samoans and Greenlanders, respectively [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there is a positive linkage between RNF10 and MetS. In addition, RNF10 has been found to be significantly enhanced in obesity and diabetes, contributing to disorders of glucose and lipid metabolism (9). Moreover, RNF10 is shown to repress cell proliferation (10).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a number of large-scale exome and whole-genome sequencing efforts to identify such rare variants underlying T2D risk within specific populations are ongoing. 25,26 Alternatively, the majority of ''missing'' heritability might instead be ''hidden'' and explained by the cumulative effect of many variants with small effect sizes. [27][28][29][30] Recently, investigators have tested this hypothesis by applying linear mixed models (LMMs), which treat individual SNP effects as random effects and allow for the estimation of total additive genetic variance.…”
Section: Introductionmentioning
confidence: 99%